2007
DOI: 10.1128/jvi.02195-06
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Calcium-Binding Site 2 in Simian Virus 40 Infection

Abstract: The exposure of molecular signals for simian virus 40 (SV40) cell entry and nuclear entry has been postulated to involve calcium coordination at two sites on the capsid made of Vp1. The role of calciumbinding site 2 in SV40 infection was examined by analyzing four single mutants of site 2, the Glu160Lys, Glu160Arg, Glu157Lys (E157K), and Glu157Arg mutants, and an E157K-E330K combination mutant. The last three mutants were nonviable. All mutants replicated viral DNA normally, and all except the last two produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…The negative-stain EM projection images of the structure of SV40 revealed that the majority of the virus (Ͼ93%) appeared as near-spherical particles ϳ45 nm in diameter, as previously described (40,41) (Fig. 3B and C and 4).…”
Section: Resultsmentioning
confidence: 90%
“…The negative-stain EM projection images of the structure of SV40 revealed that the majority of the virus (Ͼ93%) appeared as near-spherical particles ϳ45 nm in diameter, as previously described (40,41) (Fig. 3B and C and 4).…”
Section: Resultsmentioning
confidence: 90%
“…Interestingly, some of the mutants fail to enter the cell (e.g., E330K in Site 1) while others enter the cells, but fail to migrate to the nucleus (e.g., E157A-E160A and E216K in Site 2) due to an inability to bind Ca 2+ leading to premature dissociation. Thus, the binding of two Ca 2+ ions to the dual Ca 2+ -binding site on VP1 is essential for the assembly of the icosahedral capsid, as well as the cell entry and nuclear transport [103] , [119] .…”
Section: Viral Ca 2+ -Binding Proteinsmentioning
confidence: 99%
“…The removal of Ca 2ϩ from capsids could be particularly crucial for viruses that depend on metal ions for assembly and stability, such as rotavirus, mouse polyomavirus, and dragon grouper nervous necrosis virus (DGNNV) (1,39,43). A few studies have reported that mutations at the metal-binding sites decrease virus infectivity by impairing the early stages of virus-host interaction and genome release (23,24). When Ca 2ϩ is removed from the capsids of plant viruses such as cowpea chlorotic mottle virus (CCMV), tomato bushy stunt virus (TBSV), and turnip crinkle virus (TCV) by metal chelators (2,33,35), the virion swells by almost 10% and becomes susceptible to RNase.…”
mentioning
confidence: 99%